1998
DOI: 10.1021/je970117b
|View full text |Cite
|
Sign up to set email alerts
|

Viscosity and Molar Volume of Potassium Thiocyanate + Sodium Thiocyanate + Acetamide Melt Systems

Abstract: Density and viscosity of 0.25[xKSCN + (1 − x)NaSCN] + 0.75CH3CONH2 melt systems were measured as functions of temperature (293.15 ≤ T/K ≤ 343.15) and mole fraction, x = 0.0 to 1.0. The temperature dependence of viscosity has been analyzed by using the Vogel−Tammann−Fulcher (VTF) equation. Molar volumes and intrinsic volume were found to be additive in nature. The existence of the mixed alkali effect (MAE) has been established by the significant negative deviation from the additivity in the ideal glass transiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 11 publications
0
20
0
Order By: Relevance
“…From Figure 2 it is apparent that the conductivity iso-therms showed significant negative deviation (∼11-15%) and may be considered as the onset of the mixed anion effect, whereas viscosity isotherms (Figure 3) do not show any detectable mixed anion effect as lithium nitrate is progressively replaced by lithium bromide. In our earlier mixed Na/K thiocyanates in acetamide medium (Mahiuddin, 1996;Kalita et al, 1998c) we reported both positive (∼4.6% in K + rich region) and negative (∼27% in Na + rich region) deviations in electrical conductivity isotherms and ∼27-55% negative deviation in the viscosity isotherms. Plowiec et al (1985) reported that Na + in acetamide melt medium form a polymeric type solvated ion.…”
Section: Resultsmentioning
confidence: 69%
“…From Figure 2 it is apparent that the conductivity iso-therms showed significant negative deviation (∼11-15%) and may be considered as the onset of the mixed anion effect, whereas viscosity isotherms (Figure 3) do not show any detectable mixed anion effect as lithium nitrate is progressively replaced by lithium bromide. In our earlier mixed Na/K thiocyanates in acetamide medium (Mahiuddin, 1996;Kalita et al, 1998c) we reported both positive (∼4.6% in K + rich region) and negative (∼27% in Na + rich region) deviations in electrical conductivity isotherms and ∼27-55% negative deviation in the viscosity isotherms. Plowiec et al (1985) reported that Na + in acetamide melt medium form a polymeric type solvated ion.…”
Section: Resultsmentioning
confidence: 69%
“…These interesting solvent properties coupled with a wide thermal window have made molten mixtures of (acetamide + electrolyte) to be used not only as reaction media in chemical industry but also as materials for electrochemical applications at elevated temperatures. 20,21 These molten mixtures (or simply, melts) are characterized by estimated glass transition temperatures (T g ) ∼190 < T g /K < 250 range, [22][23][24][25] and are termed as supercooled mixtures as they remain in the liquid phase at temperatures much below the respective melting temperatures of the constituents. This "supercooling" phenomenon and the associated importance for chemical industry have motivated much of the research on the basic scientific aspects, because developing these melts into useful dielectric materials 13,26 requires deeper understanding of medium structural and transport properties.…”
Section: Introductionmentioning
confidence: 99%
“…The choice of this system is further motivated by the fact that density and viscosity of this mixture as a function of KSCN fraction have already been studied for a reasonably large temperature range. 44 These studies have revealed significant MAE for the composition dependent viscosity where a Vogel-Fulcher-Tammann (VFT) type of description has been found to be suitable for the temperature dependence of viscosity in these mixtures. 44 For the sake of completeness, we present in Figure S1 (Supporting Information) a plot of solution viscosity as a function of KSCN concentration, measured at ∼318 K. 44 Note also that the molten mixtures at six different fractions of KSCN considered here at 318 K are always in the liquid phase and far away from the respective glass transition temperatures.…”
Section: Introductionmentioning
confidence: 99%